THE CORRELATION BETWEEN ELEMENTS OF RACISM AND THE SPADES CARD GAMES IN TERRANCE HAYES' POEM "WE SHOULD MAKE A DOCUMENTARY ABOUT SPADES" - Danar Arief Amarullah; Shita Dewi Ratih; Ni Made Widisanti (Journal Albion : Journal of English Literature, Language, and Culture, 2021)
The research "Correlation between The Elements of Racism with Spades Card Game in the Poem by Terrance Hayes “We Should Make a Documentary about Spades” " aims to find the correlation between the Spades game and the problem of racism in the studied poetry. This research uses descriptive methods and qualitative approaches to find correlations that have been mentioned previously. This study shows in several lines, the problem of racism experienced by the black race is described by the Spades card game. This study shows that the use of the Spades card game in the poetry is closely related to slavery during colonialism and the problem of discrimination against the black race during The Great Depression. The connection between the racial issues in these two periods with the Spades card game is in the connotation of the word Spades itself which is related to slavery that occurred during the colonial period and the Spades card game which is exclusive to the black race.Keywords: Spades; Racism; Correlation; Discrimination